I of the Heart : Texts and Studies in Honor of Seyyed Hossein Nasr - Khalil, Atif,; Rustom, Mohammed,; U. Faruque, Muhammad, (Islamic History and Civilization ;, 2025)
I of the Heart is a tribute to one of the most widely respected and inﬂuential pioneers in the ﬁeld of Islamic Studies, Seyyed Hossein Nasr. For seven decades, and in over 90 books and 600 articles, Professor Nasr has drawn signiﬁcant attention to the riches of the Islamic intellectual heritage, from Suﬁsm and philosophy on the one hand, to science and art on the other. He has also been at the fore-front of discussions on several major contemporary issues, such as the environmental crisis. The forty essays in this volume, by some of the leading schol-ars in Islamic Studies today, are divided into six sections in accordance with Professor Nasr's wide range of interests and expertise: Suﬁ Theory; Suﬁ Praxis; Philosophy, Mathematics, Science; Law, Theology, Exegesis; Art, Education, Ethics; Poetry, Science, Economics.